1967
DOI: 10.1007/bf02532002
|View full text |Cite
|
Sign up to set email alerts
|

Role of ATP in the inhibition of lipogenesis in fasted animals

Abstract: This study was undertaken to obtain information both in vivo and in vitro on the role of adenosine triphosphate (ATP) in the inhibition of fatty acid synthesis in fasted mice.Fasted mice were injected intravenously with glucose or fructose or intraperitoneally with insulin to increase the supply of endogenous ATP. They then received acetate 1-(14)C, glucose 6-(3)H or fructose U-(14)C intravenously and were killed at various intervals. The controls received the labeled tracers only. The radioactivities of liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

1969
1969
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
(6 reference statements)
2
2
0
Order By: Relevance
“…In accordance with findings already published [15,16], our results have confirmed that a four-hour fast suffices to consider ably lower lipogenesis in the mouse and that essentially normal values may be restored by the addition of insulin. Furthermore, lipogenesis from glucose is more sensitive to fasting than is that from acetate.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In accordance with findings already published [15,16], our results have confirmed that a four-hour fast suffices to consider ably lower lipogenesis in the mouse and that essentially normal values may be restored by the addition of insulin. Furthermore, lipogenesis from glucose is more sensitive to fasting than is that from acetate.…”
Section: Discussionsupporting
confidence: 81%
“…The findings further suggest that ATP of different origin might not be interchangeable, ATP originating from a different source than from the oxidative chain not being utilisable for fatty acid synthesis. Decreased cellular oxidative phosphorylation might be one of the essential causes for the inhibition of lipo genesis which takes place during a short period of fasting, as already described in one of our previous publications [16]. Studies in support of the one or the other of these hypotheses are currently in progress.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…However, this is a long‐term effect resulting from down regulation of lipogenic enzymes as a consequence of inhibition of protein synthesis by cycloheximide. ATP inhibition of fatty acid synthesis was reported previously by Rous et al [26] in studies carried out with liver homogenates. Their findings, however, may not be relevant to the present study because synthesis of fatty acids under their conditions should have consumed rather than produced ATP.…”
Section: Discussionsupporting
confidence: 67%